Social Stigma on "ain’t" - Singh, Abadhesh (Himalayan Journal of Sociology and Anthropology, 2012)
'Ain't' appeared as a contraction of 'am not' around 1600 and then was extended to mean 'are not', 'is not', 'has not' and 'have not' later. In the early l8th century it began to be criticized. Though it has been disparaged and its use marks the speaker as being inferior. It has been used even by the best speakers and writers to serve useful purposes. Sociolinguistic force behind 'ain't' seems to be taking it to full acceptance. DOI: http://dx.doi.org/10.3126/hjsa.v5i0.7036 Himalayan Journal of Sociology & Anthropology-Vol. V (2012) 10-18